Dora's eggs - Sykes, Julie; Chapman, Jane, 1970- (Wilton, CT : Tiger Tales, 2002)
Dora the hen is very proud of her new eggs, but when she notices that they are not cuddly, fluffy, or wiggly like the other animals' babies, she begins to feel a little bit disappointed.
AD540L
Keywords: Chickens -- Fiction; Eggs -- Fiction; Animals -- Infancy -- Fiction; Domestic animals -- Fiction